Предмет: Алгебра,
автор: Математик34754898
3x^2+5x-2=0. 4c(c-2)-(c-4)^2
Ответы
Автор ответа:
1
3x²+5x-2=0
D= 5²-4•3•(-2)= 25+24=49
√49=7
x1= -5-7/2•3= -12/6= -2
x2= -5+7/6= 2/6= 1/3
4c(c-2)-(c-4)²=0
4c²-8c-(c²-8c+16)=0
4c²-8c-c²+8c-16=0
3c²-16=0
3c²=16
c²=8
c=±2√2
D= 5²-4•3•(-2)= 25+24=49
√49=7
x1= -5-7/2•3= -12/6= -2
x2= -5+7/6= 2/6= 1/3
4c(c-2)-(c-4)²=0
4c²-8c-(c²-8c+16)=0
4c²-8c-c²+8c-16=0
3c²-16=0
3c²=16
c²=8
c=±2√2
Математик34754898:
Спс ,но во 2 там 3с^2-16 так и остается
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: vavilinvlad2104
Предмет: География,
автор: umahanovismail56
Предмет: Математика,
автор: татьяналав